Peran Guru Kelas Rendah dalam Membimbing Bacaan dan Gerakan Salat Siswa Kelas Rendah di MI Miftahul Ulum Kota Batu - Salsabila, Helga; Asyari, Aisyah Putri (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study explores the roles of lower-grade teachers in guiding students' reading and movements during prayer at MI Miftahul Ulum Kota Batu, with a particular focus on the dhuha prayer. Teachers serve as supervisors and facilitators in the learning process, which includes teaching the correct recitations and movements associated with prayer. Additionally, the study examines the concept of classical habituation implemented by both teachers and students, along with its impact on students' ability to memorize prayer recitations. The primary objectives of this research are to evaluate the effectiveness of teacher supervision during prayer activities and to assess the influence of classical habituation on students' understanding and practice of prayer. Utilizing a qualitative approach and case study methodology, data were collected through interviews, observations, and documentation, aimed at providing in-depth insights into the effects of religious education in primary school settings. This research seeks to offer recommendations for improving teaching practices within the context of religious education.